The butterflies (Lepidoptera, Papilionoidea) of the Parque Estadual Intervales and surroundings, São Paulo, Brazil - Shirai, Leila T.; Silva, Renato O.; Dias, Fernando M. S.; Rochelle, André L. C. [UNESP]; Freitas, André V. L. (FapUNIFESP (SciELO), 2023)
The Global South has witnessed increasing sampling of its immense biological diversity during the past century. However, the diversity of many regions remains unknown, even at pristine and highly threatened places, such as in the Atlantic Forest; and for bioindicator, umbrella, and flagship groups. The present study reports the first butterfly list of the Parque Estadual Intervales, São Paulo, Brazil and surroundings, a key protected area in the last massive continuous of the Atlantic Forest. We compiled data from museums and four years of field work, under three sampling methods. We also aimed at providing resources to support conservation efforts by analyzing 27 years of climatic data (detailed in the Supplementary Material, in English and in Portuguese), discussing our results also for non-academics, and producing scientific outreach and educational material. A companion article dealt with the experiences of science outreach and capacity development, and illustrated the butterfly catalogue of the species sampled in the park. We found 312 species that sum to 2,139 records. The museum had 229 species (432 records), and we sampled 142 species (1,682 individuals), in a total effort of 36,679 sampling hours (36,432 trap and 247 net and observation hours). The richest families were Nymphalidae (148 species) and Hesperiidae (100 species). Most species were sampled exclusively by active methods (79.8%), but other sources (passive sampling, citizen science, etc.) also found unique records. We found the highest diversity metrics from January to May, and we demonstrated that winter months had less richness and abundance. We illustrated the 20 species common to all regions, and listed those that were found more than seven months in the year, as well as the most abundant species in trap sampling, with forest dwellers as well as species common to open and fragmented areas. The dominant species in our trap datasets was the iridescent white morpho, Morpho epistrophus (Fabricius, 1796), and we suggest it to become the park butterfly mascot.
As borboletas (Lepidoptera, Papilionoidea) do Parque Estadual Intervales e arredores, São Paulo, Brasil
Keywords: biodiversity knowledge shortfalls; fish carrion bait; Paranapiacaba continuum; Species list